2015
DOI: 10.1542/peds.2014-2105
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Health and Adult Education and Employment: A Systematic Review

Abstract: OBJECTIVE: Poor health in adolescence has the potential to disrupt education and employment pathways. This study is the first systematic review of the literature examining education and employment outcomes in adulthood of poor adolescent mental and physical health. METHODS:We conducted searches using a standardized search protocol in 8 electronic databases: PsycINFO, Medline, Embase, ERIC, British Education Index, Australian Education Index, Social Sciences Citation Index, and CINAHL Plus. We identified studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 62 publications
5
99
0
8
Order By: Relevance
“…132 Those who are NEET at the end of schooling are more likely to have lower earnings, greater unemployment, and employment instability through adult life. 133 Poor health and diffi cult transitions into the workplace go hand in hand; those who are NEET have high rates of mental health problems, suicide risk, and substance abuse. 134,135 …”
Section: Enabling and Protective Systemsmentioning
confidence: 99%
“…132 Those who are NEET at the end of schooling are more likely to have lower earnings, greater unemployment, and employment instability through adult life. 133 Poor health and diffi cult transitions into the workplace go hand in hand; those who are NEET have high rates of mental health problems, suicide risk, and substance abuse. 134,135 …”
Section: Enabling and Protective Systemsmentioning
confidence: 99%
“…This poor health behaviour can lead to immediate poor physical health, as well as poor health behaviours later into adulthood. Because poor health behaviours later into adulthood can beget poor adult health, the elevated chronic stress brought about by incarceration at this life stage could function to damage health far after incarceration has occurred (Haas, 2007; Hale, Bevilacqua & Viner, 2015). Given the potentially severe, negative health consequences that incarceration during the transition to adulthood could have on long-term health, more work is needed to increase our understanding of the relationship between incarceration at this transitional stage and health at this specific point in early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review has documented the negative influence poor health has on education and employment; however, most studies identified were from the USA and income outcomes were not specifically considered 5. The transition from adolescence to adulthood is a complex time period influenced by higher education attainment, personal income and family income.…”
Section: Introductionmentioning
confidence: 99%